Produktivitas Tenaga Kerja Pemasangan Marmer Metode Basah dan Kering Pada Proyek Masjid di Kota Solo - Gabriella Ananda Cahyaningtyas Kusumaningrum; Arif Yusup Ramadhan; Agung Bhakti Utama; Febri Fahmi Hakim (Universitas Islam 45, 2023)
Construction work needs to be controlled for its performance through productivity calculations in order to achieve optimal cost and time. Marble covering work has a considerable weight. However, studies discussing the calculation of labor productivity for marble covering work are still few. This study aims to determine the value of productivity, coefficients, and productivity levels of labor (Labor Utilization Rate) in completing the installation of marble coverings using the wet method for floor coverings and the dry method for wall coverings with parallel patterns and diagonal patterns. The study used a work sampling method with a productivity rating approach. Primary data were collected by sampling the volume of marble covers of 482.400 m² and observations on labor groups consisting of craftsmen and helpers in predetermined zones. Furthermore, analysis was carried out using quantitative techniques of parametric inferential statistical type where the data was confirmed to be normally distributed using SPSS software. The results showed that the labor productivity of marble floor coverings was 9.896 m² / day with a coefficient of craftsman and helper of 0.101 each and a Labor Utilization Rate of 58%. Second, the labor productivity of parallel pattern marble wall coverings is 12.589 m²/day with a coefficient of craftsman and helper of 0.159 each and a Labor Utilization Rate of 57%. The labor productivity of diagonal pattern marble wall coverings was 1,549 m²/day with the efficiency of craftsman and helper of 0.646 and the Labor Utilization Rate of 55%, respectively. The results showed that the labor of marble cover work is quite productive because it has a productivity level above 50%.